Promoting sustainable development through community- engaged workforce development - Abdul Rahman, Shukran (UM Purwokerto Press, 2019)
This paper highlights the roles of university as a centre which develops individuals and society by equipping them with necessary competencies. The paper also discusses the roles of university in relation to the Sustainable Development Goals, best carried out through community engaged activities. The paper presents the three functions of universities, namely the University Intellectual, Educational, and Social Functions. The functions can be collectively accomplished through the involvements of professional community, learned community, learning community, and community at large. The paper sheds lights on the way forward to design activities that could nurture the academic and student community to participate in community engagement activities.